Saudi Arabia's Foreign Policy Strategy: An Analysis Of Its Response To The 2011 Moratorium On Indonesian Migrant Workers Using The Allison Model - Josephira Carla Karenina; Henny Rosalinda (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2026)
This study analyzes Saudi Arabia’s foreign policy decision-making in response to Indonesia’s 2011 moratorium on migrant worker dispatch, an episode underexplored from the receiving state’s perspective. A qualitative single-case study was conducted using archival and document-based research, applying pattern-matching analysis against Graham T. Allison’s three-model framework. Saudi Arabia’s response a counter-ban issued nine days after the moratorium, concurrent diversification of labor sources, and sustained resistance to kafala reform reflects rational strategic calculation (Model I), activation of pre-existing bureaucratic Standard Operating Procedures (Model II), and internal political bargaining among actors with divergent interests (Model III). All three models are required for a comprehensive explanation. Model III findings rely on inference from public documents rather than internal Saudi sources and should be treated as analytically plausible interpretations rather than empirically verified conclusions. The single-case design limits generalizability. This study extends Allison’s framework beyond military crises to labor migration diplomacy and shifts analytical focus to the receiving state’s decision-making process, offering practical insights for Indonesia’s negotiation strategy.